The Influence of Healthcare Reforms on Patient-Health Provider Relationships in Chato and Muleba Districts, Tanzania (Tanzania Journal for Population studies and Development, 2014)
Previous studies on healthcare reforms in Tanzania reported that healthcare provision has improved significantly since the implementation of the ongoing healthcare reforms. However, the influence of the reforms on the nature of patient-health provider relationships has remained unclear. This paper uses data from a study conducted in Chato and Muleba districts to reveal the nature of the relationships and their determinants. Survey questionnaires (390) were administered to healthcare users selected from catchment areas of four health facilities by using systematic random sampling. The study findings indicate that patient-health provider relationships in the study areas are largely paternalistic in both public and private health facilities, but the level of paternalism is significantly higher in the former. Patients under exemption and waiver modes of access to healthcare significantly face more paternalism than their counterparts under user fees and healthcare insurance. A patient experiences mutual or paternalistic patient-health provider relationship depending on one’s mode of access to healthcare, the level of education, and the type of health facility one attends. Mechanisms need to be devised within the framework of the current healthcare reforms to improve patient-health provider relationships as it is an important aspect in healthcare provision.